ENHANCING STUDENTS’ SPEAKING ABILITY IN LIBYAN CLASSROOMS: EXAMINING TEACHERS’ DIFFICULTIES WITH 21ST CENTURY ENGLISH TEXTBOOKS - Basma Ali A. Almbabi; Senowarsito Senowarsito; Siti Nur'Aini (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2026)
This research examines the difficulties Libyan EFL teachers encounter in improving students’ speaking skills, using the quantitative and qualitative methods are combined to have a comprehensive understanding of the issue. To investigate real teaching practices, data were collected from 26 preparatory school teachers using a structured questionnaire, semi-structured interviews with four teachers, and seven classroom observations. The findings show that there are many challenges faced by teachers in teaching speaking effectively. These include weak students’ linguistic competence, low motivation, and speaking anxiety. Contextual constraints include large class sizes, limited time, and inadequate technological resources. Moreover, the study identifies a gap between the communicative goals of the textbooks and the realities of classroom implementation. Teachers also pointed out the lack of professional training and the marginalization of speaking skills in formal assessment practices, which further diminish opportunities for meaningful oral communication. The study concludes that textbooks are designed to foster communicative language use, but their effectiveness is still constrained by pedagogical, institutional, and environmental factors. It recommends targeted teacher training, better classroom resources, curriculum content adaptation to the students’ level of proficiency, and the integration of speaking assessment into the evaluation systems to promote students’ oral proficiency in Libyan classrooms.